Developing flash media of Quranic-based human reproduction system material - Kurniawan, Arif Didik; Muldayanti, Nuri Dewi; Putri, Banita Eka (Jurnal Pendidikan Biologi Indonesia, 2018)
The problem of implementing Islamic values in the learning process is one of the concerns in Islamic-based schools, in particular, Rahmatan Lilâalamin Islamic Senior High School in Pontianak. This study aimed to develop learning media based on the Quran verses in the human reproductive system using Macromedia flash software. This research and development used three phases of the 4D model developed by Thiagarajan, namely define, design, and development. The development results were validated by expert appraisal consisted of instructional review (appropriateness, effectiveness, feasibility) and technical review (media and language). Instruments used in this study were interview guide sheet (define phase), validation sheets, student response questionnaires, and post-test for product trial (development phase). Product trials were carried out by testing large groups consisted of 64 students majoring in social science at Rahmatan Lilâalamin Islamic Senior High School. The expert appraisal results showed that media reached âvery validâ criteria with the validation scores 83.33 (instructional review), 80.42 (media), Â and 85.00 (language). Therefore, the flash media of Quranic-based human reproductive system material is potential to be used as media in teaching Islamic values integrated within the learning process.